2019
DOI: 10.4081/mrm.2019.31
|View full text |Cite
|
Sign up to set email alerts
|

Indoor exposure to particulate matter and volatile organic compounds in dwellings and workplaces and respiratory health in French farmers

Abstract: Introduction: Few investigations have related objective assessments of indoor air pollutants to respiratory health in farmers, in spite of the many rural environmental hazards to which they are exposed. Chemical air pollution has been particularly neglected. Objective: We investigated the relationships of indoor exposure to particulate matter (PM) and volatile organic compounds (VOCs) to respiratory health in farmers. Methods: Nineteen VOCs (5 families) and PM (from ultrafine to total suspended particles (TSP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Although the most common risk factor of COPD is smoking (GOLD, 2020), some people develop COPD as a result of exposure to environmental components unique to farm environments (Cho et al, 2015). Farmers work in complex environments that expose them to multiple hazards, including organic dust, pesticides, and zoonotic pathogens (Nordgren & Charavaryamath, 2018), which have been associated with an increased risk of developing COPD (Maesano et al, 2019). Furthermore, studies have observed that farmers have a higher prevalence of COPD (5.1%) compared to the general population (2.9%), even though the prevalence of smoking among farmers is lower (Guillien et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the most common risk factor of COPD is smoking (GOLD, 2020), some people develop COPD as a result of exposure to environmental components unique to farm environments (Cho et al, 2015). Farmers work in complex environments that expose them to multiple hazards, including organic dust, pesticides, and zoonotic pathogens (Nordgren & Charavaryamath, 2018), which have been associated with an increased risk of developing COPD (Maesano et al, 2019). Furthermore, studies have observed that farmers have a higher prevalence of COPD (5.1%) compared to the general population (2.9%), even though the prevalence of smoking among farmers is lower (Guillien et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2+ ) were examined by Wei and collaborators(Wei et al 2019). Moreover, 2 studies(Maesano et al 2019;You et al 2008) analysed different families of VOCs in the atmosphere; benzene (C 6 H 6 ) and formaldehyde (HCHO) were measured in another study(Reinhardt et al 2011) and different PAHs were considered in 3 studies (de Assuncao et al 2014; Sevimoglu and Rogge 2016; Xing et al 2020). Moreover, in addition to the pollutants reported above, the presence of endotoxin (Barnig et al 2012; Pavilonis et al 2013), levoglucosan (Jimenez et al 2006), acrolein (Reinhardt et al 2011), quartz (Swanepoel et al 2011) and asbestos bers (Buczaj et al 2014) were considered as well (Table SM1 and TableSM2).…”
mentioning
confidence: 99%